Implementation of Online Learning in Elementary School Students Due To The Covid-19 Pandemic - Ekawati, Kharisma Aprilia (Universitas Sebelas Maret, 2020)
Educators must be able to adapt learning activities to any circumstances. Including in a pandemic situation like this, educators must be able to arrange fun online learning for students. The objectives of this study are (1) to describe the Covid-19 pandemic (2) to describe the concept of online learning (3) the objectives and benefits of online learning (4) the advantages and disadvantages of online learning (5) the barriers to online learning (6) the impact of online learning on students. The results of this study are the implementation of online learning for elementary school students can run well if there is cooperation between teachers, students and parents. Online learning has many challenges and obstacles that can be overcome with good cooperation between teachers and parents, an agreement is established on the learning method to be used. As a professional teacher, you must be able to arrange online learning that is fun and not boring.